2021
DOI: 10.1007/jhep07(2021)132
|View full text |Cite
|
Sign up to set email alerts
|

Gluodynamics and deconfinement phase transition under rotation from holography

Abstract: We investigate rotating effect on deconfinement phase transition in an Einstein-Maxwell-Dilaton (EMD) model in bottom-up holographic QCD approach. By constructing a rotating black hole, which is supposed to be dual to rotating strongly coupled nuclear matter, we investigate the thermodynamic quantities, including entropy density, pressure, energy density, trace anomaly, sound speed and specific heat for both pure gluon system and two-flavor system under rotation. It is shown that those thermodynamic quantities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 105 publications
1
13
1
Order By: Relevance
“…The result that the critical temperature of the confinement/deconfinement transition decrease with increasing angular velocity is in agreement with recently study of the confinement/deconfinement transition phase in rotating QCD using phenomenological models [33][34][35]. The same behaviour was found also in Nambu-Jona-Lansinio model [36], in which the critical temperature in rotating QCD decreases due to suppression of the chiral condensate.…”
Section: Analysis Of the Results And Conclusionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result that the critical temperature of the confinement/deconfinement transition decrease with increasing angular velocity is in agreement with recently study of the confinement/deconfinement transition phase in rotating QCD using phenomenological models [33][34][35]. The same behaviour was found also in Nambu-Jona-Lansinio model [36], in which the critical temperature in rotating QCD decreases due to suppression of the chiral condensate.…”
Section: Analysis Of the Results And Conclusionsupporting
confidence: 91%
“…On the other hand, the simulations of relativistic rotation on the confinement/deconfinement phase transition in gluodynamics lattice [32], using different types of boundary conditions (Open, Periodic and Dirichlet), found that the critical temperature increases with increasing angular velocity for all boundary conditions and all lattice parameters used in the calculations, showing up an opposite behaviour if compared to our result and to the other models [33][34][35][36] cited above. However, the same authors of [32] have recently presented the first lattice results in [37] (preliminary) for the confinement/deconfinement phase transition taking into account dynamical fermions.…”
Section: Analysis Of the Results And Conclusioncontrasting
confidence: 87%
“…Finally, it would be interesting to investigate how the results obtained in this paper are affected by magnetic field or angular momentum [72,73]. We also are interested in the transport coefficients, which are obtained in the hydrodynamic limit.…”
Section: Discussionmentioning
confidence: 96%
“…It is defined by requiring S(p, t) and S 0 (t) to satisfy the matching condition (4.62), which the heavy quark rotational viscosity, λ s in terms of the source or spin correlation functions -is applicable even in the strong-coupling regime, where we have the AdS/CFT correspondence as another theoretical tool [56][57][58][59], and in particular the methods first developed for holographic spin liquids in ref. [60].…”
Section: 57)mentioning
confidence: 99%